Bio-Pelleting of Brassica Rapa Seeds Using Trichoderma Inoculants for Improved Keeping Quality and Control of Pythium Damping-Off - Khor, Siew Eim (2002)
An attempt was made to study the effect of biological seed treatment on the viability and keeping quality of B. rapa and incidence of Pythium damping-off. Trichoderma virens (UPM 23) and Trichoderma harzianum (UPM 29) were used as the microbial inoculants in bio-pelleting of the seeds. UPM 23 produced greater antagonistic activity against Pythium splendens, the causal pathogen of dampingoff of B. rapa, based on the in vitro dual culture and colony degradation tests. Percentage inhibition of radial growth (PIRG) of P. splendens was 83.8% and 94.0% when co-inoculated on Potato Dextrose Agar (PDA) and Corn Meal Agar (CMA) respectively. Parasitized hyphae failed to regenerate when plated on fresh CMA medium. UPM 23 was as effective as Captan® in protecting the B. rapa seeds against Pythium pre-emergence damping-off, due to its ability to colonize the germinating seed, compete for sites and nutrients and directly parasitizing Pythium. Percentage reduction in seedling emergence was 7.0%, 14 days after sowing, as compared to the control (80.6%). There was no significant difference in percentage post-emergence damping-off of seedlings between bio-pelleted seeds or controL However, number of surviving plants at harvest was higher for UPM 23 bio-pelleted seeds relative to the other treatments. Measurement of seed viability based on germination test, electrical conductivity test, accelerated aging test and tetrazoliwn staining, showed that B. rapa seeds either Trichoderma bio-pelleted or rice flour pelleted with 10% moisture content bas better keeping quality when stored at 10°C ± 2°C, until week 24 of storage. Seed viability and quality was further improved by reducing the moisture content to 4%. Incorporation of biocontrol agents such as UPM 29 and UPM 23 in hio-pelleting, regardless of seed moisture content required low storage temperature to ensure the survival and proliferation of these inoculum on the seed surface.